Strategies and operational procedures in oral radiology to mitigate potential SARS- CoV-2 transmission - Roque-Torres, Gina Delia (2021)
Coronavirus disease (COVID-19) is highly transmissible through respiratory droplets, saliva, and aerosol particles. Infection can lead to severe acute respiratory syndrome and trigger multi-organ failure and death. Most clinical dental procedures involve contact with saliva or the generation of aerosols with saliva and blood. These airborne particles increase the risk of transmission by COVID-19 between dentists and patients. Thus, dentistry must adopt procedures to reduce transmission during dental procedures. Although these strategies may not be directly applicable to all institutions due to cultural, social, geographical, and economic differences, the underlying principles and implemented strategies remain relevant and can be adopted or modified by the institutions dealing with the current COVID-19 outbreak. The purpose of this article is to discuss one of the principal sources of COVID-19 transmission: saliva, the biofluid most frequently handled in a radiology environment. The authors also recommend strategies and operational procedures to decrease the spread of COVID-19 in a radiological routine.